Decriminalising Ornament: The Pleasures of Pattern: The sympathy of illustration. Issue 1 (1st August 2019) - Hoogslag, Nanette
This article reflects on the research exhibition Decriminalising Ornament: The Pleasures of Pattern held in the Ruskin Gallery in Cambridge in November 2018 in conjunction with the International Illustration Research Conference of the same name. It considers the role of ornament and decoration in the exhibited works and through this the essential presence of the decorative within illustration.Key is Lars Spuybroek's concept of sympathy, which he develops based on a premodern understanding of ornamentation. In response to Spuybroek's exploration of this concept, this article seeks to extend the notion of sympathy as an essential presence within illustration. Sympathy indicates a human-material relationship not just between the illustrator and the creative materials, but also in the readers connection with this decorative act in the reproduced illustration.